Hubungan Pengetahuan Ibu, Dukungan Suami dan Peran Tenaga Kesehatan dengan Akseptor KB Suntik Di Poskesdes Surau Kecamatan Muara Jaya Kab. Ogan Komering Ulutahun 2021 - Febriani Febriani; Erma Puspita Sari; Siti Aisyah Hamid (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Injectable contraception is a contraceptive device in the form of a liquid that is injected into a woman's body periodically and contains hormones. BKKBN supports being a reliable and trusted institution in realizing a balanced growing population and quality family. Factors that affect Mother's Knowledge, Husband's Support and Simultaneous Role of Health Workers with Injectable Family Planning Acceptors at Poskesdes Surau, Muara Jaya District, OKU Regency in 2021. Research This study uses a quantitative method of analytical survey with a Cross Sectional approach, using primary data with a population of 60 people and the number of samples taken using an accedental sampling technique. using injection family planning acceptors (63.3%), good maternal knowledge (70%) and supportive husband support (63.3%). Role of Health Workers value=0.012 with injectable family planning acceptors. Conclusion There is a relationship between mother's knowledge, husband's support and the role of health workers simultaneously with injecting family planning acceptors at Poskesdes Surau, Muara Jaya District, OKU Regency in 2021